Method for evaluating bonding strength between reinforced fiber and early-age cement matrix
By using a hemispherical needle pressing head and thin plate-like sample, the through-resistance value is used to evaluate the bond strength of the reinforcing fibers and early-age cement matrix, the problem of difficulty in effectively evaluating the fiber bond strength in the prior art is solved, and a more accurate evaluation of the performance of fiber-reinforced cement-based materials is achieved.
Patent Information
- Application Number
- CN202411950139.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-27
AI Technical Summary
The prior art is difficult to effectively evaluate the bonding strength between the reinforcing fiber and the cement matrix at the early age, especially when the fiber surface treatment and dispersion are greatly affected.
The bond strength of the fiber and cement matrix was evaluated by the through resistance value using a hemispherical needle and a thin plate-like sample. This method is suitable for early fiber cement slurry samples before the age of 7 days, and can more accurately reflect the interaction between fiber surface characteristics and cement slurry.
The effective evaluation of the bonding strength of reinforcing fibers and cement matrix is achieved, which can clearly distinguish the reinforcement effect of different fiber types and additives, and at the same time provides an evaluation of fiber dispersion, simplifying the sample preparation and testing process.
Smart Images

Figure CN119901570A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based material inspection, in particular to a method for evaluating the bonding strength between reinforcing fibers and an early-age cement matrix. Background Art
[0002] Cement-based materials used in transportation infrastructure in harsh environments such as freezing, salt spray, and high temperature differences are subjected to repeated traffic loads, and the performance requirements for the materials are becoming increasingly higher. Introducing millimeter-centimeter-long fibers into the material for reinforcement can significantly improve the toughness of the material to resist brittle failure of the material under repeated loads.
[0003] When reinforcing fibers are added to cement-based materials, there is also an interface transition layer structure between the fiber surface and the cement hardened body, similar to the interface transition layer structure between the aggregate and the cement matrix. Currently commonly used reinforcing fibers, such as polyvinyl alcohol fibers, polyester fibers, and polypropylene fibers, are mainly cylindrical with smooth surfaces. Due to the existence of the fiber-cement interface transition layer with relatively weak bonding strength, the fibers are easily pulled out of the cement matrix, which greatly affects the reinforcing effect of the fibers.
[0004] When evaluating the reinforcing effect of fibers, a common method is to test the bending (flexural) strength and tensile strength of cement-based materials and characterize the effect of reinforcing fibers through macroscopic mechanical performance indicators such as bending toughness. These methods are guided by corresponding standards and specifications in terms of sample preparation, maintenance, and testing processes, and generally correspond to samples with an age of more than 3 days. However, in the laboratory stage, the screening of fibers and the effects of different fiber surface treatment methods require a simple and convenient method to compare the reinforcing effects of fibers.
[0005] The Vicat instrument of the cement setting time tester uses the time when the test needle penetrates the cement paste to a specific depth during the cement setting process as the initial and final setting time of the cement. The bottom of the test needle is a round flat head with two different bottom areas. The penetration resistance meter of the concrete setting time tester presses the penetration needle into the cement mortar after the coarse aggregate is screened out to a depth of 25mm±2mm. The initial and final setting time of the concrete is when the penetration resistance reaches 3.5MPa and 28MPa respectively. The penetration needle is also a round flat head. Regardless of the Vicat instrument or the penetration resistance meter, the test needle is a round flat head and only penetrates a certain depth inside the mixture sample, which is suitable for cement setting and early hardening process.
[0006] For cement paste samples with fiber, a round flat-headed test needle such as a Vicat instrument or a penetration resistance tester is used. During the penetration process, it is easy to cut the surrounding fibers instead of providing a pulling force to the fibers. Therefore, the flat-headed penetration needle is not suitable for testing the bonding strength between the reinforcing fibers and the cement matrix. In addition, if the test needle only penetrates a certain depth into the sample, its penetration resistance can only reflect the improvement of the internal bonding force of the cement during the hydration and hardening process, but cannot effectively show the bonding strength between the fiber and the cement matrix. Summary of the invention
[0007] The present invention provides a testing and evaluation method for examining the bonding strength between reinforcing fibers and an early-age cement matrix. The indenter head is changed into a hemispherical indenter head, and the sample is adjusted into a thin plate shape (a flat fiber cement slurry sample with a thickness of 2-4 mm). The penetration resistance value (i.e., the ratio of the penetration pressure obtained by the test needle to the area of the hemispherical indenter head) obtained when the test needle penetrates the sample is used to evaluate the bonding strength between the fiber and the cement matrix.
[0008] When the penetration needle penetrates the sample, the surrounding cement matrix is subjected to complex stresses such as extrusion, splitting, and tension. The fibers therein are mainly subjected to pulling forces from different directions due to different distribution patterns. When the sample is penetrated, this force reaches a peak value. The method of the present invention is suitable for early fiber cement paste samples before 7 days old, when the strength of the cement matrix has not yet fully developed and the bonding force between the reinforcing fibers and the cement matrix still needs to be improved. The test results can better reflect the interaction and applicability of the fiber surface characteristics with the cement paste, mixed materials or additives.
[0009] Specifically, the technical solution of the present invention is as follows:
[0010] A method for evaluating the bonding strength between reinforcing fibers and early-age cement matrix, comprising:
[0011] Step S1, mixing the test fiber, cement and additives uniformly in a stirring device to obtain a fiber cement slurry;
[0012] Step S2, pouring the fiber cement slurry mixture into a mold, shaking and smoothing the surface, covering the surface of the fiber cement slurry sample with a layer of plastic film, placing it in a cement curing room (box), and demolding after curing to a specified age;
[0013] Step S3, after drawing grid lines at a certain interval on the flat fiber cement slurry sample, place it on the penetration resistance tester. The penetration needle with a hemispherical pressure head presses through the sample at the intersection of the grid at a certain rate, and the penetration pressure value (i.e., the maximum pressure value, in N) is obtained by the pressure sensor. During the penetration of the sample by the penetration needle, the surrounding cement matrix is subjected to complex stresses such as extrusion, splitting, and tensioning. Due to the different distribution patterns, the fibers are mainly subjected to pulling effects from different directions. When penetrating the sample, this force reaches a peak value. The ratio of the penetration pressure value to the area of the hemispherical pressure head is the penetration resistance value, in MPa, which is calculated by the following formula:
[0014]
[0015] Where:
[0016] f p ——Penetration resistance value, unit: MPa, calculated to an accuracy of 0.01;
[0017] N pi ——penetration pressure value when measuring point is i (i=1, 2, 3…), unit: N;
[0018] A p ——Surface area of the penetration needle indenter, mm 2 ;
[0019] Step S4: according to different molds, a certain number of penetration pressure values or penetration resistance values are obtained, and the average value, standard deviation and mean deviation rate of the penetration pressure value or penetration resistance value are calculated according to the following formula:
[0020]
[0021]
[0022] Where:
[0023] X i ——Penetration pressure value (N) or penetration resistance value (MPa, calculated to the nearest 0.01) at the ith measuring point;
[0024] N——Number of all measuring points of a single sample;
[0025] ——Penetration pressure value (N) or average penetration resistance value (MPa, calculated to the nearest 0.01) at each measuring point in a single sample;
[0026] S——Standard deviation of test value of single sample;
[0027] D——mean deviation rate of single sample test value;
[0028] Step S5: Determine the dispersion of the test value according to the size of the standard deviation, and calculate the proportion of test points with a deviation rate within 15% from the mean deviation rate. The larger the proportion, the better the fiber dispersion, and vice versa.
[0029] Furthermore, in step S1, during mixing, the water-to-binder ratio is 0.35-0.55, the volume ratio of the fiber to the mixture is 0-5%, and the mass ratio of the additive to the cement is 0-30%.
[0030] Furthermore, in step S2, the size of the mold is bottom surface (100-200 mm)×(100-200 mm), and the depth is 2 mm to 4 mm.
[0031] Furthermore, in step S3, the grid line spacing of the sample is 20 mm, the penetration needle indenter is hemispherical with a diameter of Φ3 mm to 6 mm, and the penetration rate of the penetration needle is 1 mm / s.
[0032] Further, in step S4, the number of penetration pressure values or penetration resistance values is 16-81.
[0033] Furthermore, the test fiber is an organic fiber and / or an inorganic non-metallic fiber with a diameter of micrometer level. Due to the difference in the surface properties of the fiber and the different selection of additives, when the fiber is mixed with cement, the hydration products adsorbed on the fiber surface in the cement slurry and their binding states are different, resulting in different forces for pulling the fiber out of the cement hardened slurry, which can be used to identify the binding effect between different fibers and cement slurry. The additives used are beneficial to improving the binding force between the fiber and the cement-based material, such as nano-SiO2, nano-MgO, nano-CaCO3, etc., which can produce more dense CSH gel and other products on the fiber surface and at the interface between the fiber and the cement-based material, which not only improves the roughness of the fiber surface but also increases the tightness between the fiber and the cement-based material, and can improve the dispersion of the fiber and other substances.
[0034] Furthermore, regarding the size of the standard deviation, the larger the standard deviation, the higher the dispersion of the test values and the worse the fiber dispersion. On the contrary, the smaller the standard deviation, the smaller the dispersion of the test values, the closer to the average value, and the better the fiber dispersion. The fiber dispersion effect in the sample is evaluated by the mean deviation rate, and the number of measuring points with a deviation rate within 15% is proportional to the number of all measuring points. If the calculated ratio is greater than 75%, it indicates that the fiber dispersion effect is good, so that the difference in penetration resistance values at most measuring points is small; if this ratio is between 65%-75%, it means that the fiber dispersion is good, and the penetration resistance values at most parts of the entire sample are close; and between 50%-65%, it means that the fiber dispersion effect is poor; if it is less than 50%, it indicates that the fiber dispersion is poor.
[0035] The beneficial effects brought about by the technical solution provided by the embodiment of the present invention include at least:
[0036] In the present invention, the pressure needle head is deliberately changed to a hemispherical shape and the sample is adjusted to a thin plate shape, and the penetration resistance value obtained by the test needle penetrating the sample is used to evaluate the bonding strength between the fiber and the cement matrix. During the penetration of the sample by the penetration needle, the surrounding cement matrix is subjected to complex stresses such as compression, splitting, and tension. Due to different distribution patterns, the fibers therein are mainly subjected to pulling effects from different directions. When penetrating the sample, this force reaches a peak.
[0037] The method of the present invention can not only clearly distinguish the reinforcing effects of different fiber types and different addition amounts, but also can obtain the dispersion effect of the fiber in the cement paste. The method is simple in sample preparation and convenient in the test process. It can be used for the screening of organic and inorganic non-metallic reinforcing fibers in the research and preparation of cement-based materials, and as a supplementary explanation for the improvement of tensile strength, toughness and other properties of fiber-reinforced cement-based materials.
[0038] The method of the present invention is suitable for early fiber cement paste samples before 7 days of age, when the strength of the cement matrix has not yet fully developed and the bonding force between the reinforcing fibers and the cement matrix still needs to be improved. The test results can better reflect the interaction and applicability of the fiber surface characteristics with the cement paste, mixed materials or additives. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0040] Figure 1 The present invention is a schematic diagram of the process of the indenter being a hemispherical penetration needle and a round flat-head penetration needle penetrating a sample; wherein (a) is a schematic diagram of the hemispherical penetration needle pressing into the sample, (b) is a schematic diagram of the round flat-head penetration needle pressing into the sample, (c) is a schematic diagram of the hemispherical penetration needle penetrating the sample, and (d) is a schematic diagram of the round flat-head penetration needle penetrating the sample. DETAILED DESCRIPTION
[0041] The technical solution of the present invention is described below in conjunction with the accompanying drawings.
[0042] In the embodiments of the present invention, words such as "exemplarily" and "for example" are used to indicate examples, illustrations or explanations. Any embodiment or design described as "example" in the present invention should not be interpreted as being more preferred or more advantageous than other embodiments or designs. Specifically, the use of the word "example" is intended to present the concept in a specific way. In addition, in the embodiments of the present invention, the meaning expressed by "and / or" can be both, or it can be either of the two.
[0043] In the embodiments of the present invention, "image" and "picture" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they want to express are the same. "of", "corresponding" and "corresponding" can sometimes be used interchangeably. It should be noted that when the difference between them is not emphasized, the meanings they want to express are the same.
[0044] In the embodiments of the present invention, sometimes a subscript such as W1 may be mistakenly written as a non-subscript such as W1. When the difference is not emphasized, the meanings to be expressed are consistent.
[0045] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0046] The present invention provides a test and evaluation method for checking the bonding strength between reinforcing fibers and early-stage cement matrix, and selects organic and inorganic fine non-metallic fibers. By adding additives that are conducive to the attachment of products on the fiber surface or make the boundary between the fiber and the cement-based material more compact, such as nano-SiO2, nano-MgO, nano-CaCO3, etc., the bonding force between the fiber and the cement paste is improved, and different fibers have different attachments on the fiber surface under the action of cement-based materials. The selected test fiber, cement, and additives are weighed, and put into a mixer to mix evenly with a water-cement ratio of 0.35-0.55, a fiber-mixture volume ratio of 0-5%, and an additive-cement mass ratio of 0-30%.
[0047] Pour the fiber cement paste mixture into a mold with a bottom surface of (100-200) mm × (100-200) mm and a depth of 2 mm to 4 mm. First, tap the cement paste mixture with a steel ruler, shake it, and then fill the mixture until it is full. Use the steel ruler to tap it again and scrape the surface flat. Cover the sample surface with a layer of plastic film. Place it in a cement curing room (box) and remove it from the mold after curing for 1 day. Samples with a longer age continue to be cured to the specified age.
[0048] When the Φ3-6mm pressure head penetrates the fiber cement slurry sheet, due to the effect of the fiber, the rupture range is within a circle with a radius of 10mm. Draw grid lines on the flat fiber cement slurry sample at a spacing of 20mm. Place the sample on the pad of the penetration resistance test platform. There is a Φ20mm circular hole prefabricated on the pad just below the penetration needle, and the pad is 20mm thick. When penetrating the measuring point, place the corresponding measuring point within the range of the Φ20mm circular hole on the pad. The penetration needle presses through the sample at a rate of 1mm / s at the intersection of the grid manually or electrically, and the maximum pressure value - the penetration pressure value, is obtained by the pressure sensor, in N. The penetration needle pressure head is hemispherical, with a diameter of Φ3mm to 6mm.
[0049] Figure 1 The schematic diagram of the process of the penetration needle of the present invention with a hemispherical indenter penetrating the sample is shown in the figure. The process of the penetration needle with a round flat head penetrating the sample is also shown in the figure. When the penetration needle presses into the sample, the sample under the indenter is compressed. For the hemispherical indenter, one end of the side fiber is bound by the cement hardening slurry, and the other end under the indenter is pulled downward. Figure 1 As shown in (a); for the circular indenter, the side fibers are sheared by the penetrating indenter, and some fibers are cut off, such as Figure 1 (b) When the penetration needle is pressed into the sample to a certain depth, the sample below the indenter begins to shear and fracture until it penetrates the sample. For a hemispherical indenter, this process is accompanied by different fiber distribution patterns, and the fibers are mainly subjected to pulling forces from different directions, such as Figure 1 As shown in (c), this force reaches its peak when penetrating the sample; for the circular indenter, the side fibers are cut off after being pulled, and the effect of the fibers cannot be reflected, such as Figure 1 (d) shown.
[0050] The ratio of the penetration pressure value to the hemispherical pressure head area is the penetration resistance value, in MPa, and the calculation formula is shown in formula (1). According to the molds with different bottom areas, 16 to 81 penetration pressure values or penetration resistance values can be obtained after planning the grid. The average value, standard deviation and mean deviation rate of the penetration pressure value or penetration resistance value can be obtained according to formulas (2), (3) and (4).
[0051] Finally, the degree of dispersion of the test value is judged according to the size of the calculated standard deviation, and the proportion of test points with a deviation rate within 15% is calculated from the mean deviation rate. The standard deviation and the mean deviation rate complement each other to explain the degree of dispersion of the test value relative to the mean value, and the difference in the size of the test values at each test point can show the fiber distribution. In places where the fiber distribution is more agglomerated, the pressure head needs more force to penetrate. In places where the fiber distribution is sparse, the corresponding fiber resistance to the pressure head is reduced and the penetration pressure is smaller. If the fiber dispersion is poor, the difference in penetration resistance values between the measuring points will increase. The greater the difference between the test value and the mean value and the more corresponding measuring points, the greater the corresponding standard deviation and mean deviation rate. On the contrary, the fiber dispersion is good, and the corresponding standard deviation is small in the mean deviation rate. The number of measuring points with a deviation rate within 15% is proportional to the number of all measuring points. If the calculated ratio is greater than 75%, it indicates that the fiber dispersion effect is good, so that the difference in penetration resistance values at most measuring points is small; if this ratio is between 65%-75%, it means that the fiber dispersion is good, and the penetration resistance values at most parts of the whole sample are close; and if it is between 50%-65%, it means that the fiber dispersion effect is poor; if it is less than 50%, it indicates that the fiber dispersion is poor.
[0052] For the common macro-mechanical performance indicators of bending (flexural) strength and tensile strength of cement-based materials, the reinforcing effect of fibers is evaluated. According to the cement mortar test (ISO method), the mortar is prepared, and the test fiber is mixed with cement, standard sand, and additives in a mortar mixer with a water-cement ratio of 0.5, a mortar-sand ratio of 1:3, a fiber-mixture volume ratio of 0-5%, and an additive-cement mass ratio of 0-30%. The fiber mortar mixture is poured into a 40mm×40mm×160mm mold, filled twice, and placed on a vibrator for a certain period of time. After the surface is scraped flat, a layer of plastic film is covered on the surface of the sample. Place it in a cement curing room (box), curing for 1 day, and demolding. Samples with longer early ages such as 3d and 7d continue to be cured to the specified age; after curing to the corresponding age, the mortar flexural and compressive strengths are measured by a flexural and compressive testing machine. Comparing the strength of the fiber-added group with that of the blank group can show the reinforcing effect after the fiber is added.
[0053] The test and evaluation method for checking the bonding degree between the reinforcing fiber and the early-age cement matrix of the present invention can not only clearly distinguish the reinforcing effects of different fiber types and different addition amounts, but also can obtain the dispersion effect of the fiber in the cement paste at the same time. The method is simple in sample preparation and convenient in the test process. It can be used for the screening of organic and inorganic non-metallic reinforcing fibers in the research and preparation of cement-based materials, and as a supplementary explanation for the improvement of the tensile strength, toughness and other properties of fiber-reinforced cement-based materials.
[0054] This will be described below with reference to specific embodiments.
[0055] Example 1
[0056] Use PO 42.5 cement, with a water-cement ratio of 0.5, add 2% polyvinyl alcohol fiber to the mixture, where the polyvinyl alcohol fiber length is 12mm, to prepare a fiber cement slurry. Put the weighed polyvinyl alcohol fiber and cement into a mixing pot together, use a slurry mixer, first slowly stir and then quickly stir to disperse, and finally add water and stir quickly to mix evenly. Fill the stirred mixture into a 2mm thick 100mm×180mm mold, vibrate after filling, fill it up, scrape it flat with a steel ruler, wrap it with plastic film and place it in a curing box for curing for 1d. Remove the mold, take the 1d-old sample to plan the grid, and place it on the circular gasket of the penetration resistance device, select a Φ5mm hemispherical pressure needle, and this sample can press 32 penetration pressure data.
[0057] According to formula (1), all penetration pressures are converted into penetration resistance, and the data are processed according to formulas (2), (3) and (4), and the standard deviation is calculated to be 0.17 MPa. The final average penetration resistance is 1.79 MPa, and the mean deviation rate is 86.36%. It can be seen that the measured data are concentrated near the average value, and the fiber dispersion effect is good. The 7d flexural and compressive strengths of the mortar block with the same water-cement ratio of 0.5 and 2% cement mass polyvinyl alcohol fiber are 7.67 MPa and 34.70 MPa, respectively, as shown in Table 1, which are 23.1% and 39.9% higher than the blank group without fiber.
[0058] Example 2
[0059] The other conditions are the same as those in Example 1, except that 2% of the 12mm polyvinyl alcohol fiber added to the mixture is replaced by 2% of the cellulose fiber in the mixture, wherein the length of the cellulose fiber is 5mm. A certain amount of cellulose fiber is first weighed and soaked in a sealed bottle with a certain amount of water for 24 hours, then dispersed with an egg beater at a speed of 22r / s, and then added to cement and stirred evenly with a pure slurry mixer. The evenly stirred mixture is filled in a 2mm thick 120mm×120mm mold. This sample can be pressed to obtain 25 penetration pressure data.
[0060] All penetration pressures were converted into penetration resistance according to formula (1), and the data were processed according to formulas (2), (3) and (4) to obtain a standard deviation of 0.85, an average penetration resistance of 1.41 MPa, a mean deviation rate of 70.6%, and good fiber dispersion. At the same water-cement ratio, the 7d flexural and compressive strengths of the mortar block when the cellulose fiber content was 2% were 7.19 MPa and 34.10 MPa, respectively, which were 15.4% and 37.5% higher than those of the blank group.
[0061] Example 3
[0062] The other conditions are the same as those in Example 1, except that 2% of the 12 mm polyvinyl alcohol fiber added to the mixture is replaced by 2% of the 6 mm long polyester fiber added to the mixture. The mixture after being stirred evenly is filled in a 3 mm thick 100 mm × 100 mm size mold. This sample can be pressed to obtain 16 penetration pressure data.
[0063] All penetration pressures were converted into penetration resistance according to formula (1), and the data were processed according to formulas (2), (3) and (4) to obtain a standard deviation of 0.28, an average penetration resistance of 3.45 MPa, a mean deviation rate of 75%, and a concentrated distribution of values at each measuring point, indicating good fiber dispersion. The 7d flexural and compressive strengths of the mortar block at a polyester fiber content of 2% at the same water-cement ratio were 6.55 MPa and 31.42 MPa, respectively, which were 5.1% and 26.7% higher than those of the blank group, respectively.
[0064] Example 4
[0065] Compared with Example 1, the Φ5mm hemispherical pressing needle is replaced with a Φ4mm hemispherical pressing needle, which is filled in a 2mm thick 120mm×140mm mold. This sample can obtain 30 penetration pressure data.
[0066] According to formula (1), all penetration pressures are converted into penetration resistance, and the data are processed according to formulas (2), (3) and (4) to obtain a standard deviation of 0.79 MPa, an average penetration resistance of 2.97 MPa, and a mean deviation rate of 60%. The dispersion becomes worse when the amount of fiber added increases. From the results, it can be seen that as the diameter of the pressure needle decreases, the dispersion of the measured penetration resistance value is greater, and the accuracy and responsiveness are lower than those of the pressure needle with a diameter of 5 mm.
[0067] Example 5
[0068] Compared with Example 1, the evenly stirred mixture was filled in a 2 mm thick mold instead of a 3 mm thick 140 mm × 140 mm mold, and the Φ5 mm hemispherical pressing needle was changed to a Φ4 mm hemispherical pressing needle. This sample can obtain 35 penetration pressure data.
[0069] According to formula (1), all penetration pressures are converted into penetration resistance, and the data are processed according to formulas (2), (3) and (4) to obtain a standard deviation of 0.86MPa, an average penetration resistance of 5.87MPa, a mean deviation rate of 68.18%, and fiber dispersion deteriorates. As the sample thickness increases, the fiber dispersion deteriorates. This may be because the fiber dispersion becomes more complicated with the increase in thickness. More fibers will agglomerate in some places and the overlap between fibers will become more complicated, while in other places, the fiber distribution is less, resulting in a greater discreteness of the measured penetration resistance. In this embodiment, the length of the fiber far exceeds the thickness of the sample, and the fiber dispersion is uneven, which can easily increase the influence of the cumulative effect of the fibers in the thickness direction. In addition, the smaller the diameter of the pressure needle, the larger the deviation value.
[0070] Comparative Example 1
[0071] The other conditions are the same as those in Example 1, except that no fiber is added to the prepared cement mixture. No data can be measured for this sample. When the pressure needle penetrates with a certain force, the entire sample is broken and no data can be measured, that is, the test cannot be performed. The test block without fiber is brittle. The 7d flexural and compressive strengths of the blank group mortar blocks without fiber at the same water-cement ratio are 6.23MPa and 24.80MPa respectively.
[0072] Comparative Example 2
[0073] Other conditions are the same as those in Example 1, except that the semi-spherical pressure needle is replaced by a round flat-head pressure needle. Filled in a mold of 120 mm × 180 mm, this sample can measure 40 penetration pressure values.
[0074] The data processed according to formula (2), (3) and formula (4) have a standard deviation of 0.97 MPa, an average penetration resistance of 3.85 MPa, and a mean deviation rate of 53.85%. The deviation rate and error of the values measured by the flat-head pressure needle are greater than those of the hemispherical pressure needle, and the measured data are more inaccurate. First, the flat-head pressure needle is sharper than the hemispherical one. When pressing through the fiber cement slurry sample, it is easier to cut the fiber and penetrate the sample at the place where the fiber is less dispersed. At this time, the fiber does not play its role and is destroyed. At the place where the fiber is more distributed, it is difficult to cut off the large amount of fiber. In this way, using a flat-head pressure needle will reduce the mean deviation rate and it is difficult to accurately express the fiber dispersion effect. Secondly, when penetrating the sample, the flat-head pressure needle uses the entire plane as the contact surface to press through. When pressing into the measuring point with a large fiber content, it is difficult to penetrate, which increases the penetration pressure; and penetrating the place where the fiber is less distributed will cause the cracking range to increase, so it is more difficult for the flat-head pressure needle to test the bonding effect between the fiber and the cement matrix. The spherical indenter penetrates the sample slowly at the contact point, which makes the penetration and destruction range of the circular indenter much larger than that of the hemispherical indenter.
[0075] Comparative Example 3
[0076] Other conditions are the same as those in Example 1, except that the 2% polyvinyl alcohol fiber dosage is changed to 3%, and the stirred mixture is filled in a 140mm×140mm mold with a thickness of 3mm, and the Φ5mm hemispherical pressing needle is changed to a Φ4mm hemispherical pressing needle. This sample can obtain 35 penetration pressure data.
[0077] According to formula (1), all penetration pressures are converted into penetration resistance, and the data are processed according to formulas (2), (3) and (4). The standard deviation is calculated to be 0.95 MPa, the final average penetration resistance is 6.19 MPa, and the mean deviation rate is 58.82%. It can be seen that the measured data are concentrated near the average value, and the fiber dispersion effect is poor. This experiment did not make a better dispersion treatment for the fibers. A large number of long fibers are difficult to disperse in the cement slurry, corresponding to the poor dispersion effect. The 7d flexural and compressive strengths of the mortar block with the same water-cement ratio of 0.5 and 3% cement mass of polyvinyl alcohol fiber are 6.83 MPa and 30.23 MPa, respectively, as shown in Table 1, which are 9.6% and 27.8% higher than the blank group, respectively.
[0078] Table 1 Comparison between the embodiments of the present invention and the comparative examples
[0079]
[0080] The reinforcing effect and dispersing effect of the fiber are related to factors such as the surface properties, specifications, addition amount, and stirring process of the fiber cement slurry. Under the same stirring process and test conditions, the reinforcing effect and dispersing effect of the polyvinyl alcohol used in the test are better than those of the other two fibers. For the same fibers and test conditions, the stirring process can be changed and the stirring process can be optimized by the method provided by the present invention.
[0081] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for evaluating the bonding strength between reinforcing fibers and early-age cement matrix, characterized in that: include: Step S1, mixing the test fiber, cement and additives uniformly in a stirring device to obtain a fiber cement slurry; Step S2, pouring the fiber cement slurry mixture into a mold, shaking, flattening the surface, laminating, curing to a specified age and demoulding; Step S3, grid lines are drawn on the flat fiber cement slurry sample at a certain interval, and on the penetration resistance meter, a hemispherical penetration needle is used to press through the sample at the intersection of the grid lines at a certain rate to obtain a penetration pressure value or a penetration resistance value; Step S4, according to a certain number of penetration pressure values or penetration resistance values obtained, the average value, standard deviation and mean deviation rate of the penetration pressure value or penetration resistance value are obtained: Step S5: determine the degree of dispersion of the test value according to the size of the standard deviation, and calculate the proportion of test points with a deviation rate within 15% from the mean deviation rate.
2. The method according to claim 1, characterized in that In step S1, during mixing, the water-to-binder ratio is 0.35-0.55, the volume ratio of the fiber to the mixture is 0-5%, and the mass ratio of the additive to the cement is 0-30%.
3. The method according to claim 1, characterized in that In step S2, the mold size is 100-200 mm × 100-200 mm on the bottom and 2 mm to 4 mm in depth.
4. The method according to claim 1, characterized in that: In step S3, the grid line spacing of the sample is 20 mm, the penetration needle indenter is hemispherical with a diameter of Φ3 mm to 6 mm, and the penetration rate of the penetration needle is 1 mm / s.
5. The method according to claim 1, characterized in that In step S4, the number of penetration pressure values or penetration resistance values is 16-81.
6. The method according to claim 1, characterized in that The test fibers are organic fibers and / or inorganic non-metallic fibers with a diameter of micrometers.
7. The method according to claim 1, characterized in that In step S5, the smaller the standard deviation value is, the better the fiber dispersion is; the higher the proportion of the number of measuring points with a deviation rate within 15% to the total number of measuring points is, the better the fiber dispersion effect is.
8. The method according to claim 1, characterized in that The early stage is no more than 7 days.
Citation Information
Patent Citations
Testing device and method for bonding performance of fiber and mortar materials
CN102628790A
Method for determining interface bonding force of composite material reinforcement and matrix
CN110940585A
Testing method for accurately measuring adhesive property of superfine polyethylene fiber and cement-based composite material
CN115165497A
Method suitable for detecting dispersity of fibers in ECC material mixture
CN118443914A
Method for testing microscopic bonding performance of fiber and cement-based material
CN119104488A
Cited By
Selection method and evaluation method of fiber and additive for cement-based material based on characteristics of surface attachments
CN121275447A